Assessment of radioactivity in commercially available honey in Italy. (April 2020) - Meli, Maria Assunta; Desideri, Donatella; Battisti, Paolo; Giardina, Isabella; Gorietti, Daniela; Roselli, Carla
Abstract: Activity concentration of natural radionuclides and 137 Cs were estimated in 28 honeys purchased from large supermarket chains in Italy. Uranium, polonium and thorium were measured by alpha spectrometry, 4 0  K and 137 Cs by gamma spectrometry and 226 Ra by liquid scintillation. The concentrations were 50.6 ± 46.3, 0.023 ± 0.010, 0.019 ± 0.017, 0.27 ± 0.40 Bqkg −1 for 4 0  K, 238 U, 234 U and 210 Po respectively. 235 U, 228 Th, 232 Th were consistently <0.007 Bqkg −1 and 226 Ra <0.200 Bqkg −1 . 137 Cs was <2.1 Bqkg −1 in 93% of the samples. The activity of radiocesium was found to be above the minimum detectable level in only two samples and did not exceed the highest permitted level for food contributing to the overall radioactivity only slightly. The effective doses attributable to 210 Po accounts for 0.0026–5.31% of global human exposure to natural radiation. The honeys that were tested were found to be of good quality with regard to the parameters under study, confirming the general image of honey as a genuine healthy product. Highlights: Radiological characterization was done in honey from Italian supermarkets. Radionuclides were detected in honey in a wide range of activity. 137 Cs was below the minimum detectable activity concentration in 93% of the samples. The 210 Po doses account for 0.003–5.3% of the world natural radiation exposure. The honeys from large-scale retail trade in Italy were of good quality and safe.